(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Recent advances in hematology have significantly improved the diagnosis and management of coagulation disorders, hematologic malignancies, and abnormal bleeding conditions. A comprehensive coagulation workshop and Continuing Medical Education (CME) program held at the Himalayan Institute of Medical Sciences, Swami Rama Himalayan University, Dehradun, on 10–11 August 2024, brought together experts and participants from across Uttarakhand to discuss contemporary developments in coagulation diagnostics, flow cytometry, hematology analyzers, and personalized therapeutic approaches. The workshop emphasized practical training in coagulation assays, mixing studies, inhibitor screening, and global hemostasis testing. The CME sessions focused on hypercoagulability, lymphoma diagnosis using flow cytometry, management of abnormal bleeding, and modern hematology diagnostics. Important advances in flow cytometric evaluation of B-cell and T-cell lymphomas, anticoagulation strategies, and automated laboratory technologies were highlighted. The event provided a platform for knowledge exchange, skill development, and discussion of innovative diagnostic and therapeutic strategies aimed at improving patient outcomes in hematologic disorders.